EKSISTENSI KOMUNITAS MUSLIM DAN HINDU - Yusuf Bachtiar; Anak Agung Bagus Wirawan; Ida Ayu Putu Mahyuni (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2022)
Pegayaman Village is one of the villages located in Sukasada District, Buleleng Regency, Bali Province which is also one of the Muslim villages in Bali. This study discusses the uniqueness of Pegayaman Village and the potential possessed by Pegayaman Village both from the natural potential and the potential possessed based on the results of acculturation between Balinese and Muslim cultures. This research is a qualitative type using interviews, observations and literature studies in the data collection process. The results showed that the factors behind the acculturation between the Balinese Muslim and Hindu communities in Pegayaman Village were genetic factors, in this case the Pegayaman Muslim community believed and acknowledged that their ancestors were Balinese, especially from the mother's lineage, while the father's lineage was the soldiers from Blambangan. Meanwhile, the form of acculturation that makes Pegayaman Village very unique is that the naming system given to children has similarities with the name Bali. In addition, the Subak system can be found in Pegayaman Village and the building architecture is a mixture of Bugis, Balinese and Javanese. The forms of acculturation found in Pegayaman Village not only create their own uniqueness but can also be developed as a village that can be one of the locations in studying the application of tolerance values.